Correlating The Synthesis Protocol And Properties Of Polyimide Film For CO2 Removal - Yiauw, Diing Ye (Universiti Sains Malaysia, 2018)
Polyimide membrane has a wide variety of applications, especially in natural gas industry for removing CO2. Although polyimide membrane has been widely studied and used in the industry, the influence of its synthesis protocol on the properties of polyimide film that are in favor of CO2 removal is still roughly understood. Hence, polyimides with different monomer combinations were synthesized via both thermal imidization and also chemical imidization in order to discover its impact on the properties of the polyimide film that were important for CO2 removal. The results showed that the final polyimide molecular weight was affected by the imidization methods, which the conditions offered by each method played a major role in the growth of polyimide chain. The polyimide chain length then contributed to the membrane density, although it was also governed by other factors such as monomer structure and intermolecular interactions. Furthermore, the type of imidization also governed the intermolecular packing, which was found to be an critical factor that determined the membrane free fractional volume (FFV). The permeability and also selectivity were strongly dependent on FFV, which it served as the characteristic that allowed the tradeoff between the membrane selectivity and permeability. In addition, cross-linking the polyimide membrane via furnace treatment was also one of the dominant attributes in deciding the membrane FFV. It was concluded that properties of polyimides, their membrane formation, and hence gas separation performance were able to be controlled and improved by their synthesis protocol.